2022
DOI: 10.1177/08901171211041424
|View full text |Cite
|
Sign up to set email alerts
|

Parental Education and Child Physical Health Following the BP Deepwater Horizon Oil Spill

Abstract: Purpose: To assess whether trajectories of children’s physical health problems differ by parental college degree attainment in Louisiana areas highly impacted by the 2010 BP Deepwater Horizon oil spill (BP-DHOS). Design: Three waves of panel data (2014, 2016, and 2018) from the Gulf Coast Population Impact / Resilient Children, Youth, and Communities studies. Setting: BP-DHOS-impacted communities in coastal Louisiana. Participants: Parents of children aged 4-18 in a longitudinal probability sample (n = 392). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…[2][3][4][5] Few panel studies exist and even fewer cover more than 1 or 2 years, thus, much remains unknown about the long-term DHOS effects on health. [6][7][8][9] Exceptions include a panel study of women following the DHOS which found ongoing elevated symptoms of depression and mental distress up to 6 years following the spill. 10 Panel studies with probability samples including both women and men are especially lacking in extant research.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Few panel studies exist and even fewer cover more than 1 or 2 years, thus, much remains unknown about the long-term DHOS effects on health. [6][7][8][9] Exceptions include a panel study of women following the DHOS which found ongoing elevated symptoms of depression and mental distress up to 6 years following the spill. 10 Panel studies with probability samples including both women and men are especially lacking in extant research.…”
Section: Introductionmentioning
confidence: 99%